(untitled) (Texas Journal of Medical Science, 2022)
Communicable diseases remain a public health concern around the world, especially after the recent Covid-19 emergency. Therefore, this study was conducted in order to assess people’s awareness of the infection with the emerging corona virus. In this cross-sectional study, 350 adults from different regions of Salah al-Din Governorate were included through a written questionnaire. They answered the eight questions asked in the survey paper, which were about some important facts about the coronavirus. The results proved that (68%) of the participants in the study had infected with covid-19, and that most of them had died in their relatives. Thus, most of them (92%) were aware of the risk of this emerging virus. About 86% of them had received vaccination against this infection, and (72%) of them were aware of the benefit of the vaccine in in preventing infection. A reasonable percentage (65%) of them was following the disease update. Nevertheless, the majority of individuals (90%) were knowledge of procedures to avoid infection. Thus, this study concluded that the majority of participants are aware of the important facts of Covid-19 and there is little need for them to be more aware of them.